Diffusion of democracy : the past and future of global democracy - Wejnert, Barbara 1956- (Cambridge Univ. Press, 2014)
"This book explores the course and causes of the worldwide diffusion of democracy through an assessment of the political and economic development of individual countries from the year 1800 to 2005. Using this extended range of data and examining multiple variables Barbara Wejnert creates a conceptual model for the diffusion of democracy and to measure national democratization. The author characterizes each nation's political system, its networking with other countries, level of development, and media advancement, in order to pinpoint what leads to national and regional progress to or regress from democratization. Her innovative findings challenge established thinking and reveal that the growth of literacy does not lead to democratization but is instead an outcome of democracy. She also finds that networks between non-democratic and democratic states are more important to a nation's democratization than financial aid given to non-democratic regimes or the level of national development"--